Predicting the consequences of default - Pistunov, Ihor; Nadelyaeva, Daria (LAP LAMBERT Academic Publishing, 2020)
Data on defaults in Argentina, Uruguay, Russia, Mexico have been collected. According to these date, models have been developed to forecast the rate of decline in GDP per capita, consumer price index, wages and national currency and against the US dollar. These models have been applied to predict a possible default in Ukraine. The forecast showed that 0.86 likely to default in 2020 and the country’s economy to reach 2019 is possible no earlier than 2025.
Keywords: дефолт; валовий внутрішній продукт; індекс споживчих цін